“Meleti” Speech and Language Development Support System - Kyriacou, Efthyvoulos C.; Charalambous, Marina; Theodorou, C.; Iliophotou, C.; Ioannou, Maria; Hadjichristofi, George (My University, 2013)
Through this study we are presenting a system that intents to support and monitor speech and language development of children with hearing impairment using hearing aids and/or cochlear implants, or children with language delays. The scope is to support children during their daily life. The system is mainly based on a set of applications for Android devices. These applications can be used anywhere the child and the parents are and they include several tasks presented to the child as a game. The main goal is to support sessions being done by the caregivers like reproducing words, sounds, small phrases etc. The system was created based on the four levels targeted during speech and language support sessions (auditory skills, receptive language, expressive language, speech / articulation). The results from system usage are being recorded from a server where specialists can monitor get results and act accordingly in order to improve the child’s performance. Initial design and development steps have been completed. The two first levels of the system have been tested on a small group of user with very encouraging results. Furthermore the development of several other modules related to the levels of language development will continue in order to cover all language development levels.
Keywords: Disabled Children; Early Intervention; Early Childhood Special Education